Peran Guru Dalam Pembentukan Akhlak Santri di Pondok Pesantren At-Taqwa Candung - Salsa Dia Novita; Feni Ayu Monia; Biyah Siti Murbiyah (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The background of this research is to pay attention and require attention, namely the phenomena that occur in Islamic boarding schools, especially the At-Taqwa Candung Islamic boarding school. This thesis focuses on the role of the ustadz/ustadzah in developing the morals of students at the At-Taqwa Candung Islamic Boarding School, what factors support and hinder the role of the ustadz/ustadzah in developing the morals of the students at the At-Taqwa Candung Islamic Boarding School. This type of research is field research. In an effort to obtain the information and data needed for this material, this research approach uses qualitative methods. The results of the research found that the strategies of ustadz/ustadzah in Islamic boarding schools vary by carrying out the stages and methods that have been determined as closely as possible in order to achieve the desire to produce students who have good morals, become role models in taking notes, advising, and teaching the sciences of morality. While the inhibiting and supporting factors are the existence of students who are still enthusiastic about learning in Islamic boarding schools, and sufficient books, adequate places of worship, and so on, the inhibiting factors are the teaching and learning process, inadequate facilities and infrastructure, and little space. classes, lack of qualified teachers, professional teachers and so on.